Clinical Nutrition in Critical Care Medicine – Guideline of the German Society for Nutritional Medicine (DGEM). (October 2019) - Elke, Gunnar; Hartl, Wolfgang H.; Kreymann, K. Georg; Adolph, Michael; Felbinger, Thomas W.; Graf, Tobias; de Heer, Geraldine; Heller, Axel R.; Kampa, Ulrich; Mayer, Konstantin; Muhl, Elke; Niemann, Bernd; et al.
Summary: Purpose: Enteral and parenteral nutrition of adult critically ill patients varies in terms of the route of nutrient delivery, the amount and composition of macro- and micronutrients, and the choice of specific, immune-modulating substrates. Variations of clinical nutrition may affect clinical outcomes. The present guideline provides clinicians with updated consensus-based recommendations for clinical nutrition in adult critically ill patients who suffer from at least one acute organ dysfunction requiring specific drug therapy and/or a mechanical support device (e.g., mechanical ventilation) to maintain organ function. Methods: The former guidelines of the German Society for Nutritional Medicine (DGEM) were updated according to the current instructions of the Association of the Scientific Medical Societies in Germany (AWMF) valid for a S2k-guideline. According to the S2k-guideline classification, no systematic review of the available evidence was required to make recommendations, which, therefore, do not state evidence- or recommendation grades. Nevertheless, we considered and commented the evidence from randomized-controlled trials, meta-analyses and observational studies with adequate sample size and high methodological quality (until May 2018) as well as from currently valid guidelines of other societies. The liability of each recommendation was described linguistically. Each recommendation was finally validated and consented through a Delphi process. Results: In the introduction the guideline describes a) the pathophysiological consequences of critical illness possibly affecting metabolism and nutrition of critically ill patients, b) potential definitions for different disease phases during the course of illness, and c) methodological shortcomings of clinical trials on nutrition. Then, we make 69 consented recommendations for essential, practice-relevant elements of clinical nutrition in critically ill patients. Among others, recommendations include the assessment of nutrition status, the indication for clinical nutrition, the timing and route of nutrient delivery, and the amount and composition of substrates (macro- and micronutrients); furthermore, we discuss distinctive aspects of nutrition therapy in obese critically ill patients and those treated with extracorporeal support devices. Conclusion: The current guideline provides clinicians with up-to-date recommendations for enteral and parenteral nutrition of adult critically ill patients who suffer from at least one acute organ dysfunction requiring specific drug therapy and/or a mechanical support device (e.g., mechanical ventilation) to maintain organ function. The period of validity of the guideline is approximately fixed at five years (2018–2023).